Mouse models for abdominal aortic aneurysm - Golledge, Jonathan; Krishna, Smriti Murali; Wang, Yutang (British journal of pharmacology, 2022)
Abdominal aortic aneurysm (AAA) rupture is estimated to cause 200,000 deaths each year. Currently, the only treatment for AAA is surgical repair; however, this is only indicated for large asymptomatic, symptomatic or ruptured aneurysms, is not always durable, and is associated with a risk of serious perioperative complications. As a result, patients with small asymptomatic aneurysms or who are otherwise unfit for surgery are treated conservatively, but up to 70% of small aneurysms continue to grow, increasing the risk of rupture. There is thus an urgent need to develop drug therapies effective at slowing AAA growth. This review describes the commonly used mouse models for AAA. Recent research in these models highlights key roles for pathways involved in inflammation and cell turnover in AAA pathogenesis. There is also evidence for long non‐coding RNAs and thrombosis in aneurysm pathology. Further well‐designed research in clinically relevant models is expected to be translated into effective AAA drugs. LINKED ARTICLES This article is part of a themed issue on Preclinical Models for Cardiovascular disease research (BJP 75th Anniversary). To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v179.5/issuetoc Innate and adaptive immunity, autophagy, protease‐mediated extracellular matrix remodelling, hydroxyapatite‐mediated microcalcification, epigenetic changes, and intraluminal thrombus are strongly implicated in abdominal aortic aneurysm (AAA). Immune response regulators, autophagy promoting agents, protease inhibitors, siRNA inhibiting hydroxyapatite formation, microRNAs, and coagulation cascade inhibitors have been reported to limit AAA development in mice.